Improving spin-transport by disorder - Chadov, Stanislav; Kiss, Janos; Felser, Claudia (Advanced Functional Materials, 2013)
A new scheme dedicated to improving spin-transport characteristics by applying random disorder as a constructive agent is reported. The approach paves the way for the construction of novel systems with a surprising combination of properties, which are either extremely rare or even entirely absent within the known classes of ordered materials: half-metals with no net magnetization and magnetic semiconductors. As a real case example for the applicability of the scheme, it is shown that a series of such materials can be derived from the tetragonal Heusler compound Mn3Ga by substituting Mn with a 3d-transition metal. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: conductivity; electron localization; magnetoresistance; spin-transport